The effect of androgen excess on maternal metabolism, placental function and fetal growth in obese dams - Romina Fornes (Nature Portfolio, 2017)
Abstract Pregnant women with polycystic ovary syndrome (PCOS) are often overweight or obese. To study the effects of maternal androgen excess in obese dams on metabolism, placental function and fetal growth, female C57Bl6J mice were fed a control (CD) or a high fat/high sucrose (HF/HS) diet for 4–10 weeks, and then mated. On gestational day (GD) 15.5–17.5, dams were injected with dihydrotestosterone (CD-DHT, HF/HS-DHT) or a vehicle (CD-Veh, HF/HS-Veh). HF/HS dams had higher fat content, both before mating and on GD18.5, with no difference in glucose homeostasis, whereas the insulin sensitivity was higher in DHT-exposed dams. Compared to the CD groups, the livers from HF/HS dams weighed more on GD18.5, the triglyceride content was higher, and there was a dysregulation of liver enzymes related to lipogenesis and higher mRNA expression of Fitm1. Fetuses from HF/HS-Veh dams had lower liver triglyceride content and mRNA expression of Srebf1c. Maternal DHT exposure, regardless of diet, decreased fetal liver Pparg mRNA expression and increased placental androgen receptor protein expression. Maternal diet-induced obesity, together with androgen excess, affects maternal and fetal liver function as demonstrated by increased triglyceride content and dysfunctional expression of enzymes and transcription factors involved in de novo lipogenesis and fat storage.